Investor psychology, point and figure charting in the Singapore stock market. - Han, Junguang. (2008)
Through the use of point & figure charts, we attempt to examine the predictive power of chart patterns discovered in the prices of all Singapore stocks listed between 1973 to 2005. Specifically, we look into the impact of time, types and trends of signals on such predictive power.